The Impact of Parental Involvement in Online Learning on Student Academic Success - Nur Rohmatillah; Musmulyadin Musmulyadin; Chandra Halim Maharaja; Sabri Sabri; Krim Ulwi (Journal of Computer Science Advancements, 2023)
Online learning is learning conducted through the internet. Online learning is also commonly referred to as e-learning, online learning, distance learning, virtual learning, and so on. Based on the explanation of online learning, parental involvement is also needed when students implement online learning. This study was conducted with the aim to find out how parental involvement can help students be more involved in online learning. In addition, it also aims to find out how parental involvement can impact on students’ academic success. The method used in this research is quantitative method. This method is a way of collecting numerical data that can be tested. Data is collected through the distribution of questionnaires addressed to students. Furthermore, the data that has been collected from the distribution of the questionnaire, will be accessible in Excel format which can then be processed with SPSS. From this study conducted, the researcher was able to obtain the results of the study on the impact of parental involvement in online learning on students’ academic success showed that parental involvement has a positive and significant influence on students’ academic achievement. In addition, parental involvement can help students in increasing students’ motivation to learn, improve students’ cognitive and psychomotor abilities, and help students face challenges in online learning. Based on the results of this study, it can be concluded that the impact of parental involvement in online learning on students’ academic success has a significant effect on students’ academic success. Parents play an active role in helping their children study at home, providing students with mobile phones and internet quota, and monitoring their academic progress. In addition, they provide supervision, incentives, and guidance which are very important for online learning.